Prognostic value of multi-PLD ASL-based cerebral perfusion ASPECTS in acute ischemic stroke - Li, Qingqing; Jiang, Chaojun; Qian, Linqing; Yang, Jing; Mu, Tianchi; Dong, Congsong; Wang, Shu; Wang, Zhenyu; Liu, Hengheng; Dong, Yijun; Dai, Zhenyu; Chen, Fei (Frontiers in Neurology, 2024)
Early CT Score (ASPECTS) based on multiple post-labeling delay (multi-PLD) arterial spin labeling (ASL) for outcome assessment in acute ischemic stroke (AIS) patients.The endpoint was modified Rankin scale score at 90 days (90-day mRS).Patients were divided into the good outcome (0 2) and poor outcome (3 6) groups. The independent samples t-test, Mann-Whitney U-test, and χ 2 test were used to compare clinical and imaging parameters between groups. We used partial correlation analysis to evaluate the relationships between ASPECTS and outcomes. Multivariate logistic regression analysis was used to examine potential independent prognostic indicators.The receiver operating characteristic (ROC) curve analysis was used to evaluate the performance of the independent prognostic indicators in predicting outcomes.Results: 55 AIS patients were included. The good outcome group had a lower baseline National Institutes of Health Stroke Scale (NIHSS) (Z = -3.413, P < 0.001) and infarct core volume (ICV) (Z = -3.114, P = 0.002) as well as higher cerebral blood flow (CBF)-ASPECTS (Z = -3.835, P < 0.001) and cerebral blood volume (CBV)-ASPECTS (Z = -4.099, P < 0.001). Higher CBF-ASPECTS (r = -0.459, P = 0.001), and CBV-ASPECTS (r = -0.502, P < 0.001) were associated with a lower 90-day mRS. The baseline NIHSS, CBF-ASPECTS, and CBV-ASPECTS were identified as independent prognostic indicators. The AUCs of the baseline NIHSS, CBF-ASPECTS, and CBV-ASPECTS were 83.3%, 87.4%, and 89.9%, respectively. Combining NIHSS with CBF-ASPECTS and CBV-ASPECTS, the AUC significantly improved to 96.3%. The combined three factors showed a significant difference compared to the baseline NIHSS (Z = 2.039, P = 0.041) and CBF-ASPECTS (Z = 2.099, P = 0.036), but no difference with CBV-ASPECTS (Z = 1.176, P = 0.239).The ASPECTS based on multi-PLD ASL is a valuable tool for identifying independent prognostic indicators and assessing clinical outcomes in AIS patients. The baseline NIHSS, combined with CBF-ASPECTS and CBV-ASPECTS, enhances the predictive efficacy of clinical outcomes in AIS patients. The CBV-ASPECTS alone can offer comparable predictive efficacy to the combination.